Severe IgG4-Related Disease in a Young Child: A Diagnosis Challenge - Susana Corujeira; Catarina Ferraz; Teresa Nunes; Elsa Fonseca; Luísa Guedes Vaz (Case Reports in Pediatrics)
Immunoglobulin G4-related disease (IgG4-RD) is an increasingly recognized syndrome that can appear with multiple organ involvement, typically with tumor-like swelling, lymphoplasmacytic infiltrate rich in IgG4-positive plasma cells, and elevated serum IgG4 concentrations. We report the case of a 22-month-old female child with failure to thrive and recurrent respiratory tract infections since 8 months of age. Physical examination was normal except for pulmonary auscultation with bilateral crackles and wheezes. Laboratory tests revealed elevated erythrocyte sedimentation rate, and elevated serum IgG and IgG4 with polyclonal hypergammaglobulinemia. Thoracic CT and MRI showed multiple mediastinal lymphadenopathies and a nodular posterior mediastinal mass in right paratracheal location with bronchial compression. Initial fine needle aspiration biopsy was compatible with reactive lymphadenopathy but after clinical worsening a thoracoscopic partial resection of the mass was performed and tissue biopsy revealed lymphoplasmacytic infiltrate and increased number of IgG4-positive plasma cells and a ratio of IgG4/IgG positive cells above 40%. Glucocorticoids therapy was started with symptomatic improvement, reduction in the size of the mass, and decrease of serum IgG4 levels after 6 weeks. There are very few reports of IgG4-RD in children. Long-term follow-up is necessary to monitor relapses and additional organ involvement.